178k views
1 vote
A spring-mass system with k1 and m has a natural frequency of ωn. If a second spring k2 is added in series with the first spring, the natural frequency is lowered to 1/2*wn. Determine k2 in terms of k1.

2 Answers

1 vote

Answer:


k_(2) = (1)/(3)k_(1)

Solution:

Natural frequency of a spring mass system is given by:


\omega = \sqrt{(k)/(m)} (1)

Now, with a system with
k_(1) and mass m, natural frequency is:


\omega_(n) = \sqrt{(k_(1))/(m)} (2) (given)

Also, when another spring
k_(2) is added in series with the first one the natural frequency of the system reduces to
(\omega_(n))/(2), spring's equivalent stiffness is given by:


(1)/(k_(eq))= (1)/(k_(1)) + (1)/(k_(2))


k_(eq) = (k_(1)k_(2))/(k_(1) + k_(2))

Therefore,


(\omega_(n))/(2) = \sqrt{(k_(eq))/(m)}


\omega_(n) = 2\sqrt{(k_(eq))/(m)} (3)

From eqn (2) and (3):


\sqrt{(k_(1))/(m)} = 2\sqrt{(k_(eq))/(m)}


\sqrt{(k_(1))/(m)} = 2\sqrt{(k_(1)k_(2))/(m(k_(1) + k_(2)))}

Squaring both sides of the above eqn, we get:


(k_(1))/(m) = 4(k_(1)k_(2))/(m(k_(1) + k_(2)))


k_(1)^(2) = 4k_(1)k_(2) - k_(1)k_(2) = 0

Solving the above equation in order to get the relation between
k_(1) and
k_(2):


k_(1) = 3k_(2)

Therefore,
k_(2) in terms of
k_(1):


k_(2) = (1)/(3)k_(1)

User Eyosiyas
by
5.0k points
3 votes

Answer:


K_2=(K_1)/(3)

Step-by-step explanation:

When only one spring is connected with mass


\omega _n=\sqrt{(K_1)/(m)}

When another spring is added in series with spring one ,then the equivalent spring constant is K

Given that final natural frequency become half


\omega_f=\sqrt{(K)/(m)}


\omega_f=(1)/(2)\omega _n


K=(1)/(4)K_1 -----(1)

We know that equivalent spring constant for series connection is given as


K=(K_1K_2)/(K_1+K_2) -----(2)

By using equation 1 and 2 we can say that


K_2=(K_1)/(3)

User Rscnt
by
5.1k points